Antibiotic susceptibility pattern of bacterial isolates from quantitative culture of bronchoalveolar lavage fluid in patients with clinical suspicion of pneumonia - Jha, Beena; Sharma, Manisha; Sapkota, Jyotshna; Pant, Subash; Neopane, Arpana (Journal of Kathmandu Medical College, 2020)
Background: The common bacterial pathogens isolated from bronchoalveolar lavage (BAL) include Klebsiella pneumoniae, Acinetobacter baumanii, Pseudomonas aeruginosa and Coagulase negative Staphylococcus.Objectives: This study was conducted to identify pneumonia causing organisms and to determine their antibiogram.Methodology: A descriptive cross-sectional study was carried out at Kathmandu Medical College Teaching Hospital, Kathmandu, Nepal over a period of one year (Aug 2019-Jul 2020). Ethical approval (Reference Number:1004201810) was taken and convenience samplin g was done using Clinical and Laboratory Standards Institute(CLSI) guidelines. Data were analyzed using Statistical Package for Social Sciences(SPSS) version 19.Results: Out of 32 BAL samples, 14 were culture positive. The commonest bacterial pathogens isolated were Klebsiella Pneumoniae 6(42.85%), followed by Acinetobacter baumanii 5(35.71%), Pseudomonas aeruginosa 2(14.28%) and Coagulase negative Staphylococcus 1(7.14%). The isolates were 100% sensitive to Tigecycline and Polymixin B followed by Colistin(92.85%). Cotrimoxazole was 100% resistant to these isolates followed by Azithromycin (92.85%.Conclusion: Klebsiella pneumomiae, Acinetobacter baumanii were the most common bacterial pathogens isolated from BAL.